Reframing embodied learning in a blended learning environment to facilitate and promote decolonial practices in graphic design in higher education, South Africa - Du Plessis, Mia (Stellenbosch : Stellenbosch University, 2026)
Thesis MA (VA) --Stellenbosch University, 2026.